THE LEARNING STYLE OF HIGH ACHIEVER STUDENTS OF ENGLISH DEPARTMENT OF IAIN SAMARINDA - Umar Fauzan; Rostanti Toba; Nirmayana Nirmayana (English Review: Journal of English Education, 2020)
Learning style is the method of a person to get solutions from problem-solving in process of learning. In this case, students’ learning styles have closely relation to their achievement. In this research, the researchers focus on the the type of learning styles of high achiever students of the English department at IAIN Samarinda. This is a survey research where the researchers collected by usig the Perceptual Learning Style Preference Questionnaire. The subject of this research is the high achiever students of the English Department at IAIN Samarinda that consists of twenty-two students from fifth and seventh semester students. This research found that all of learning styles exist in this research results where visual learning style become the highest percentage among others. Students’ learning habits in everyday life also play important role in determining their learning style. Research discussion and suggestion are provided further in this study.